The remarkable adsorption capacity of zinc/nickel/copper-based metal–organic frameworks for thiophenic sulfurs. Issue 107 (7th November 2016) - Wang, Tingting; Fang, Yaoyao; Dai, Wei; Hu, Lifeng; Ma, Na; Yu, Le
Abstract : A Zn/Ni/Cu-BTC MOF containing three central metals and 1, 3, 5-benzene tricarboxylic acid was synthesized and its adsorption performance for thiophene, benzothiophene and dibenzothiophene (DBT) from three model oils was systematically studied. Abstract : A new type of Zn/Ni/Cu-BTC metal–organic framework (MOF) with three central metals (Cu 2+, Zn 2+ and Ni 2+ ) and one organic ligand (1, 3, 5-benzene tricarboxylic acid, H3 BTC) was synthesized and its adsorption performance for thiophene (Th), benzothiophene (BT) and dibenzothiophene (DBT) from three typical model oils was systematically studied using breakthrough curves. Due to its coordinatively unsaturated sites, Zn/Ni/Cu-BTC possesses a high sulfur capacity. In addition, it shows a strong durability in the presence of aromatic components and moisture. The saturated adsorbents could be easily regenerated with solvent washing and nitrogen sweeping. The results of this study revealed that Zn/Ni/Cu-BTC is a promising adsorbent for the removal of thiophenic sulfurs from fuels.